STUDY OF KINETICS MODEL OF FLAVONOID TOTAL RELEASE IN PATCH OF ANTIHYPERTENSIVE HERBS - Dian Eka Ermawati; Anif Nur Artanti; Dyah Ayu Ambarwati; Niken Rosyana Dewi Septini; Sholichah Rohmani; Wisnu Kundarto (Sanata Dharma University, 2021)
The liquid extract of antihypertensive herbs could reduce blood pressure equivalent to Hydrochlorothiazide 25 mg based on research conducted in “Hortus Medicus” clinic, Tawangmangu, Central Java, but parameters of herbal medicine taste, design, and packaging had the lowest scores. Transdermal patch was chosen as an alternative to resolve those problems. Polymers determined the effectiveness of the active substance release from the formula. Patch was formulated from combination of hydrophilic hydroxy methylcellulose (HPMC) and carboxymethylcellulose natrium (CMC-Na) polymer which would produce a fast release profile. The objective of this research was to study the kinetics models of total flavonoid release and to study the total number of flavonoids released from the antihypertensive herbs patch for 5 hours, as well as to determine the optimum formula for observing the weight, pH and loss on drying. Herbs were infused with distilled water at 90 ° C for 15 minutes, filtered then evaporated. Release kinetics model used a modified type-5 dissolution apparatus equipment with a cellophane membrane. The optimum proportion of HPMC and CMC-Na was 220:180 mg. Patch was dark brown, circle shaped, moist and flexible. It had pH value of 7.29 ± 0.09, folding endurance of 350, and thickness of 0.64 ± 0.05 mm. The average percentage of total flavonoids released from the matrix patch was 37.23% for 5 hours. The release kinetics followed the Higuchi kinetics model with a diffusion mechanism.